KEPEMIMPINAN IDEAL PADA ERA GENERASI MILENIAL - Ni Putu Depi Yulia Peramesti; Dedi Kusmana (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2018)
ABSTRACT Leadership is an important part of the management process and is needed in all types of organizations. Leaders plan and organize existing resources by influencing and directing others to achieve optimal subordinate performance. Leadership success is influenced by the leadership style applied and the satisfaction of subordinates. Being a good leader in the generation of millennials today and in the future is a critical challenge. Along with the times, many leaders emerged due to demands and environmental conditions at that time. In the era of millennial generation, effective governance will be realized if leaders can fulfill qualifications as credible leaders, have the ability, intellectual, and vision that is far ahead. But a good leader must also have integrity, honesty, and loyalty to the interests of the people. Millennial leadership needs to support the independence and entrepreneurial spirit of the millennial generation. Building a nation must have the main foundation of independence and entrepreneurship. Keywords: leadership, millennial generation, ideal leaders.